Politics of Rightful Killing : Civil Society, Gender, and Sexuality in Weblogistan - Shakhsari, Sima, 1968- (Book collections on Project MUSE., 2020)
"In the early 2000s, mainstream international news outlets celebrated the growth of Weblogistan--the online and real-life transnational network of Iranian bloggers--and depicted it as a liberatory site that gave voice to Iranians. As Sima Shakhsari argues in Politics of Rightful Killing, the common assumptions of Weblogistan as a site of civil society consensus and resistance to state oppression belie its deep internal conflicts. While Weblogistan was an effective venue for some Iranians to "practice democracy," it served as a valuable site for the United States to surveil bloggers and express anti-Iranian sentiment and policies. At the same time, bloggers used the network to self-police and enforce gender and sexuality norms based on Western liberal values in ways that unwittingly undermined Weblogistan's claims of democratic participation. In this way, Weblogistan became a site of cybergovernmentality, where biopolitical security regimes disciplined and regulated populations. Analyzing on-line and off-line ethnography, Shakhsari provides an account of digital citizenship that raises questions about the internet's relationship to political engagement, militarism, and democracy"--